Efektivitas Promosi Melalui Media Sosial Instagram Dengan Menggunakan Pendekatan Epic Model (Studi Kasus Pada Garden Café) - Syaiful Haq; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  Promotion can be said as one of the determining factors for the success of a marketing program to provide information about the existence of a product. Social media is one of the most widely used promotional tools. Technological developments encourage marketers to be creative in advertising by utilizing social media. Advertising on social media requires strategy and effort to appeal both emotionally and rationally to foster buying interest in social media users. People in Indonesia are quite active in using Instagram. The popularity of Instagram is seen by business people as an effective opportunity to promote the products of their business. This study uses a qualitative method with a case study approach at the Garden Café. Data collection is done by interview, observation and documentation study. There were 4 research participants, namely the Garden Café Manager and 3 Garden Café customers who were willing to become research participants. Based on the results of research on the Effectiveness of Promotion through Instagram social media using the epic model at the Garden Café. The promotional strategy implemented at the garden café is effective if measured using the dimensions of Empathy, Persuasiveness, Impact, Communication Keywords: promotion, social media, epic model